Intact stability - Moore, Colin S. (Principles of Naval Architecture series, 2010)
Written by Dr. Colin S. Moore, Manager, Advanced Analysis and Salvage Engineering at Herbert Engineering Corp. and a member of SNAME ad hoc committees on Double Hull Intact Stability and Parametric Rolling, the new volume in the PNA series discusses various effects on stability, such as changes in hull geometry, changes in weight distribution, suspended weights, partial support due to grounding or drydocking and free liquid surfaces in tanks or other internal spaces. The concept of dynamic stability is introduced, starting from the ship s response to an impulsive heeling moment. The effects of waves on resistance to capsize are discussed noting that, in some cases, the wave effect may result in diminished stability and dangerous dynamic effects.